THE ROLE OF PARENTS IN CHILDREN'S GROWTH AT RAUDLATUL ISLAMIC PRE-SCHOOL - Kholifah, Siti; Yulianti, Sari; Rosita, Rosita; Nurhaelah, Nurhaelah; Rasitah, Hj; Rahmawati, Rahmawati; Muhayah, Siti; Yuliyanti, Siti Nur; Julaeha, Eha; Fadilah, Siti Fadilah; Khotimah, Siti; Anipah, Aan (Yayasan Education and Social Center, 2025)
Parents significantly influence the growth and development of early childhood, particularly during the